(3LeGd GdYfbs - (3YHO GdcQje, CdaJs; (3GdYWjaj, MGJes; (3Thbj, CMeOs ((3GdbGgQIs (3OGQ GdaGQhbs, 2004)
(3gPg GdSdSdI JbOe WQb JLejd CLRGA GdLSe hGdeMGaXI Ydi LeGdgG hQYGjJgG UMjkG, ceG JbOe fUGFM NGUI HGdeMGaXI Ydi ehGVY GdLeGd aj GdLSe, hYdGL GdeTGcd GdJj JYGfj efgG GdaJGI ceTcdGJ GdTYQ hSbhWg hJbUag hcjajI YdGLg, Ch eTcdGJ GdHTQI hfYheJgG, Ch XghQ HbY ajgG heTcdGJ GdbOejf heG bO jUjHgeG ef fTbbGJ Ch NThfI(B.. (3Edi ZjQ Pdc ef GdeTcdGJ GdJj JDQb cd aJGIs
1 2 3 6 8 9 10 11 12 14
Keywords: (3GdLdOs -- (3YfGjIs; (3GdLeGds; (3GdeQCIs